The drug paradox: an introduction to the sociology of psychoactive substances in Canada - Bruno, Tara L. (Canadian Scholars, 2018)
"The Drug Paradox examines both the empirically founded and socially constructed nature of drugs and drug use in Canada, highlighting the often contradictory aspects of laws, policies, and programming that aim to address drug use. The authors explore Canada's drug paradox, where drugs and drug use are viewed as both normal and problematic. They argue that Canada's punitive approach to addressing drug use continues to exist alongside harm reduction strategies, and these competing approaches ultimately impede Canada's ability to deal effectively with substance misuse. Using a sociological and policy oriented approach, while also emphasizing the utility of a multifaceted bio-psycho-social model, this text provides students with a basic foundation in the sociology of psychoactive substances in the Canadian context. It provides an in-depth review of various areas of research that are important for students to consider when trying to make sense of the competing discourses on drugs in society."--